WORSHOP MANAJEMEN PUBLIKASI PENELITIAN DAN PENGABDIAN BERBASIS OJS DI ST3B - Frangky Silitonga; Suhendra; George Rudi Hartono Pasaribu; Steven; Robertus Suryady (JURNAL BEATITUDES, 2022)
In this workshop, the publication of scientific writing for research and service based on OJS uses OJS V.3.3 from PKP. The OJS that have been owned by ST3B are OJS Tabgha, Imparta and Beatitudes, these OJS are the objects of this service. In this activity, the devotees collaborate on two different institutions, between Karimun University and ST3B, this was done as a forum for detecting the detailed needs of ST3B for publications. The service methods used are interview, role play and demonstrative as well as direct practice using a personal account on OJS that has been registered at every OJS ST3B. The results obtained are participants are able to register, submit articles, then the editorial board plays a role in the process of managing OJS on a regular basis and arrangements. Limited time and instruments used during service can be minimized with the enthusiasm of the workshop participants and a family atmosphere to jointly advance ST3B in research publications and service using OJS that already exists in ST3B